دراسة موعد وديناميكية التمايز الزهري في صنفي العنب المحليين حلواني وبلدي - محفوض محمد; مخول جرجس; الرضوان نوفل (Latakia University Journal -Biological Sciences Series, 2019)
نُفذت هذه الدراسة في مركز البحوث العلمية الزراعية بحمص، على صنفي العنب المحليين حلواني وبلدي التابعين للنوع Vitis vinifera. L المرباة على شكل عرائش بهدف دراسة موعد وديناميكية التمايز الزهري . بدأ التمايز الزهري في الصنفين المدروسين في بداية شهر تموز (بعد العقد بحوالي أربع أسابيع) وانتهى في بداية شهر آب (بدء النضج) . تأخرت العيون القاعدية لكلا الصنفين المدروسين بالتمايز الزهري . اتبعت عيون كلا الصنفين نفس الديناميكية في التمايز الزهري . This study was carried out at Agricultural Research Center – Homs, on two grape local varieties, Halwani and Baladi which reared on arbor – system. The purpose is to study the time and dynamism of flower differentiation . The flower differentiation started from the first of June (after the setting about four weeks) to the first of August (beginning of maturiy period) . The basis eyes were late for two experimental varieties by the flower differentiation and as such side eyes in Baladi variety started November . The eyes of two varieties followed the same dynamism of flower differentiation .